MOTIF DAN KEPUASAN MASYARAKAT KOTA DENPASAR TERHADAP SINETRON “SIAPA TAKUT JATUH CINTA” DI SCTV - Br Tarigan, Della Ayu Lopiga; Amanda Gelgel, Ni Made Ras; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2019)
ABSTRACT The soap opera of “Siapa Takut Jatuh Cinta” which has aired on SCTV tv station successfully captivated the audience with a high rating on the first episode. This soap opera has violated the prevailing norms in Indonesia for several times. However, the rating still stays in the top position. In this research, the author wants to know how is the motive and the satisfaction of people who live in Denpasar City about the soap opera “Siapa Takut Jatuh Cinta”. The author use the theory of Uses and Gratifications to see what the audience want to the media. This research is conducted by measuring the motives and satisfaction of 348 respondents in Denpasar City aged 16-34 years using 4 indicators of Uses and Gratifications theory by Greenberg and Woods (1999), these are escape, social learning, social excitement, and habit. This research use descriptive quantitative methods. The sampling technique in this study is purposive sampling. The data in this research is obtained by spreading questionnaires using a Likert scale. The data analysis technique using at the average score of motive and satisfaction. The results showed that respondents aged 16-34 years in Denpasar do not get satisfaction after watching the soap opera. That thing is happened due to respondents watching the soap opera of “Siapa Takut Jatuh Cinta” only to seek entertainment and fill their spare time. If it viewed from the indicators in every aspect of the motives, there are several indicators of motives that are satisfied, such as indicators of avoiding family problems, indicators of having a friend, indicators of eliminating boredom in spare time and other indicators. Keywords: motive, satisfaction, Denpasar, the soap opera “Siapa Takut Jatuh Cinta”, SCTV